Supernumerary proteins of mitochondrial ribosomes - Rackham, Oliver; Filipovska, Aleksandra (Biochimica et biophysica acta, 2014)
Messenger RNAs encoded by mitochondrial genomes are translated on mitochondrial ribosomes that have unique structure and protein composition compared to prokaryotic and cytoplasmic ribosomes. Mitochondrial ribosomes are a patchwork of core proteins that share homology with prokaryotic ribosomal proteins and new, supernumerary proteins that can be unique to different organisms. In mammals, there are specific supernumerary ribosomal proteins that are not present in other eukaryotes. Here we discuss the roles of supernumerary proteins in the regulation of mitochondrial gene expression and compare them among different eukaryotic systems. Furthermore, we consider if differences in the structure and organization of mitochondrial genomes may have contributed to the acquisition of mitochondrial ribosomal proteins with new functions. The distinct and diverse compositions of mitochondrial ribosomes illustrate the high evolutionary divergence found between mitochondrial genetic systems. Elucidating the role of the organism-specific supernumerary proteins may provide a window into the regulation of mitochondrial gene expression through evolution in response to distinct evolutionary paths taken by mitochondria in different organisms. This article is part of a Special Issue entitled Frontiers of Mitochondrial Research. •Mitochondrial ribosomes are different from cytoplasmic and prokaryotic ribosomes.•Supernumerary proteins are unique to mitochondrial ribosomes.•We discuss the roles of mammalian-specific proteins in mitochondrial function.